Serum Thrombopoietin Level Is Not Regulated by Transcription but by the Total Counts of both Megakaryocytes and Platelets during Thrombocytopenia and Thrombocytosis - Nagata, Yuka; Shozaki, Yuka; Nagahisa, Hiroshi; Nagasawa, Toshiro; Abe, Tsukasa; Todokoro, Kazuo (Thrombosis and Haemostasis, 1997)
Thrombopoietin (Tpo) regulates platelet production, but the mechanisms regulating the serum Tpo level and platelet count in circulation have been a subject of debate. Tpo was reported to be expressed mainly in liver and kidney, but we found that Tpo is expressed in all tissues examined: abundantly in liver, kidney, muscle, colon, brain and intestine, and moderately in bone marrow, spleen, lung, stomach, heart, thymus, ovary, and endothelial and leukemic cell lines. The levels of Tpo transcripts in major Tpo producing organs, liver and kidney, and in the platelet production sites bone marrow and spleen, were constant during acute thrombocytopenia induced by anti-platelet monoclonal antibody administration in mice, and during thrombocytosis induced by Tpo injection. Furthermore, we noticed that platelet count is not exactly inversely proportional to serum Tpo level. During acute thrombocytopenia, serum Tpo level transiently increased a few hours after antibody injection, and returned to the basal level just when matured megakaryocytes accumulated in bone marrow and spleen but the platelet count was still low. Matured megakaryocytes in bone marrow and spleen increased when the serum Tpo level decreased, and decreased when platelet count rebounded. Taken together with other observations, we propose here a modified version of Kuter and Rosenberg’s theory, that is, Tpo is constitutively expressed in a variety of organs throughout the body, even in acute thrombocytopenia and thrombocytosis, and that the serum Tpo level is not regulated by Tpo gene expression nor only by platelet counts in circulation, but by the total counts of both megakaryocytes in bone marrow and spleen and of platelets in circulation